Flota de altura. Breve reseña de la evolución histórica y operatividad durante el período 1981/1982 - Bertolotti, María Isabel (1986)
This work was carried out in order to analize the ship incorporation history to the Argentine fishery fleet and the ship building policies in Argentine shipyards and ship importations. From fresher trawler fleet and freezer trawler fleet analysis we estimated optimum catch, possible catch, and natural stock for each fleet. A modern fresher fleet might reach the present value of the optimum catch, but it would not satisfy the total inshore fish factories demand unless equitable ratio between the optimum catch capacities of the fresher trawler fleet and the freezer trawler fleet be established.